Social orientation of the marketing and its role in the competitive strategies - جثير سعدون حمود; حسين مهدي حنون (Journal of Economics and Administrative Sciences, 2018)
This research shed light on the relationship between the social orientation of the marketing (interests of the Organization ,the welfare of society, satisfaction the customer) strategies competitive dimensions of (cost leadership strategy, differentiation strategy, focus and strategy), As well as to to seek to achieve a number of knowledge and applied goals, and represented the field research problem extent of interesting researched the application of social orientation and interest in achieving competitive strategy and omission of this interest in the hotels the surveyed Organization, Based on this problem, and to clarify the relationship between the main and subsidiary research variables was formulated three hypotheses of president of branched out reported (8) sub-hypotheses. Questionnaire was adopted as a tool in data and information related to research collection, it was subjected to a test validity and reliability, And distributed to a sample of (85) individual first class hotels managers in Baghdad and managers of departments and managers of the people and their assistants in the six five-star Iraqi hotels are: "Rashiad Hotel, Babylon Hotel and Ishtar Hotel, and Palestine Hotel, Hotel Baghdad, the Mansour Hotel," research using the statistical software a ready data analyzed (SPSS-19) and the Programme (Excel) is the most important statistical tools used in the analysis are:, Statistical methods have spawned number of results Perhaps the most prominent and that there were significant correlation between the social orientation of the marketing strategies competitive, as it turned out that there are significant effect between the social orientation of the marketing strategies and competitive, There are significant differences between the average answers socially oriented marketing dimensions (the organization’s interests and welfare of the community, and customer satisfaction) in the first class hotels surveyed, as there are significant differences between the average answers competitive strategies and dimensions (cost leadership strategy, differentiation strategy, focus strategy) in the surveyed hotels. In the framework of the discussion of Research the results provided a number of recommendations including the need to interesting the surveyed hotels to keep the social orientation of the market and its role in supporting and building strategies selected competitive.